Design and Optimization of a Planar Cable Robot - Kassem, Mohamad Hassan (2020)
A Master of Science thesis in Mechatronics Engineering by Mohamad Hassan Kassem entitled, “Design and Optimization of a Planar Cable Robot”, submitted in July 2020. Thesis advisors is Lotfi Romdhane and Mohammad Jaradat. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).